Dampak Implementasi Program Permindo Night Market Terhadap Pendapatan Pedagang Kaki Lima (PKL) Di Kawasan Permindo - Nayoan Suandi; Zikri Alhadi (Jurnal Teori dan Riset Administrasi Publik, 2021)
There are complaints from the people who are the targets in the implementation of the Permindo Night Market program, especially shop-house traders and parking attendants who state that the Permindo Night Market does not have a positive impact on increasing their income. This study aims to see the impact of the implementation of the Permindo Night Market Program on the income of street vendors in the Permindo area. This research method is qualitative. This study found that the success of the implementation of the Permindo Night Market program was only felt by street vendors. Meanwhile, the target of the Permindo Night Market program planned by the Padang City Government is not only street vendors, but also shop-house traders and parking attendants as people who seek income on Jalan Permindo